Kurkumin dan Inflammatory Bowel Disease - Stevani Febeline; Winda Trijayanthi Utama; Waluyo Rudiyanto (CV. Jasa Sukses Abadi, 2021)
Inflammatory Bowel Disease (IBD) is an inflammatory disease of the gastrointestinal tract. The exact cause of Inflammatory Bowel Disease is not yet known clearly. The diagnosis of inflammatory bowel disease is often delayed due to non-specific and intermittent symptoms. There are 2 types of IBD, namely Ulcerative Colitis and Crohn's Disease. Management of IBD can be done with drug therapy, surgery, or a combination of both. This therapy aims to reduce symptoms, improve quality of life, prevent disease recurrence and avoid complications. IBD treatment can occur over a long period of time, during which time it costs quite a bit and can cause various side effects that can be experienced by patients. Therefore, experts began to consider other alternative therapies that could be used, for example the use of curcumin compounds. Curcumin is the active pigment that gives turmeric its yellow color, a plant that belongs to the ginger family or Zingiberaceae and contains anti-inflammatory substances. The mechanism of action of curcumin is by suppressing activity of Nuclear Factor-Kappa B (NF-KB) and also plays a role in suppressing Interleukin-1 (IL-1), IL-6, IL-12, IL-17, and Tumor Necrosis Factor Alpha (TNF). -α), two major cytokines that play an important role in the regulation of the inflammatory response. Management of IBD can be done through the administration of drugs so that curcumin can be considered as one of the treatments for IBD.